Reaktualisasi Nilai Pendidikan Keluaraga Perspektif al-Qur’an Surah At-Tahrim Ayat 6 - Mohammad Arjati Firmansyah; Nasrulloh (Al-Kindi, 2026)
The increasing phenomenon of gadget addiction in children causes character degradation, such as decreased empathy, discipline, and social skills. QS. At-Tahrim verse 6 contains the principles of Qur'anic parenting that emphasize responsibility, control, and maintaining family morals. This study aims to analyze the reactualization of the values of QS. At-Tahrim verse 6 as a solution to overcome the negative impact of gadget use on children's character development in the digital era. The research method used is qualitative research with a library research approach, through thematic analysis of primary sources in the form of the Qur'an and tafsir books, as well as secondary sources in the form of scientific journals and contemporary parenting literature relevant to the issues of character education and digital literacy. The results of the study indicate that the values of ri'ayah (supervision), wiqayah (prevention), and role models can be reactualized as an applicable Islamic parenting framework in shaping children's character amidst the challenges of the digital era.